Estrategias de promoción turística para la reactivación económica en el Estero Salado de Guayaquil - Granados Santillan, Kevin David (2021)
The Estero Salado is one of the most popular tourist places within the city of Guayaquil, which, like several tourist places in the country, presents a reduction in the number of tourist visits, among the factors that influence this is the The Covid 19 pandemic is also the inadequate promotion strategies or lack of tourism promotion strategies. Tourism promotion strategies allow the power to potentiate tourism within a sector or place, and this in turn allows the power to develop the local economy, in this case with the application of tourism promotion strategies within Estero Salado to make known to this tourist spot in addition to the development of this would be potentiated as well. Within the tourist promotion strategies is the use of technological tools such as digital media, for example social networks, web pages, traditional media such as TV, radio, online TV, among others, which can potentiate tourism and economic development d the tourist places in this case the development of the Estero Salado, but for this the work of the set of local and governmental authorities is needed to be able to achieve the proposed objective.